SPICA Joint European/Japanese Workshop 2009
DOI: 10.1051/spica/200904019
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Mid/Far IR Blind, Wide Area, Spectral Surveys in Breaking the Confusion Limit

Abstract: Source confusion determines the useful depth to which to take large-area extragalactic surveys. 3D imaging spectrometers, with positional as well as spectral information, however, can potentially provide a means by which to break the traditional confusion limit.In this poster we present the results of our investigation into the effectiveness of mid/far infrared, blind, wide area spectroscopic surveys with SAFARI in breaking through the confusion limit. We generate an artificial sky representative of 100 SAFARI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The spectra used in this work are a sub-sample of those used in Raymond et al (2009) and are shown in Figure 1. We selected the following 6 spectra to represent each of the principle classes of object; normal (eg.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The spectra used in this work are a sub-sample of those used in Raymond et al (2009) and are shown in Figure 1. We selected the following 6 spectra to represent each of the principle classes of object; normal (eg.…”
Section: Methodsmentioning
confidence: 99%
“…These spectra are highlighted in Figure 1 by a thicker line. Details as to how the spectra were compiled are given Raymond et al (2009).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations